ANALISIS PENILAIAN TINGKAT KESEHATAN BANK PADA PT. BANK MUAMALAT SYARIAH, Tbk CABANG DENPASAR - Lestari, Eka Puji; Rahyuda, Henny (E-Jurnal Manajemen, 2012)
The banking sector has a huge potential and opportunities in its role as a source of financing for the public and business sectors. Since many banks are liquidated when the monetary crisis, Bank Indonesia made ??more incentive to restructure the banking system is expected to bring strong banking structure, effective, efficient, and healthy. Soundness of a bank can be assessed through a qualitative approach to the management factors and quantitative approach to the factors of capital, asset quality, management, earnings and liquidity, known as CAMEL analysis. The research was conducted at Jalan Teuku Umar Denpasar with the purpose of research to determine the health of PT. Bank Syariah Muamalat Tbk Branch Denpasar period 2007-2011 in terms of aspects of capital, asset quality, management, earnings and liquidity. The analysis technique used is descriptive analysis of the data analyzed by describing the results of the calculation of financial ratios. The results of this study indicate that in general the PT. Bank Syariah Muamalat Tbk Branch Denpasar predicated healthy. Through analysis tools CAMEL ratios, the final assessment of the health of PT. Bank Syariah Muamalat Tbk Branch Denpasar period 2007-2011 amounted to 96.6 percent, 94.86 percent, 96.2 percent, 96.71 percent and 95.5 percent. Keywords: Assessment , Health Level